Drug delivery for cancer therapeutics - Aminabhavi, Tejraj (Henry Stewart Talks, 2021)
Cancer Therapeutics, Drug Delivery Mechanisms, Drug Development, Liposomes, Nanoparticles, Nanotechnology, Nanotoxicology, Niosomes, Dendrimers, Micelles, Routes of Drug Delivery